Cardiac Interventions for Patients With Trisomy 13 and Trisomy 18: Experience, Ethical Issues, Communication, and the Case for Individualized Family-Centered Care. Issue 1 (January 2022) - Cleary, John P.; Janvier, Annie; Farlow, Barbara; Weaver, Meaghann; Hammel, James; Lantos, John
This report is informed by the themes of the session Trisomy 13/18, Exploring the Changing Landscape of Interventions at NeoHeart 2020—The Fifth International Conference of the Neonatal Heart Society. The faculty reviewed the present evidence in the management of patients and the support of families in the setting of trisomy 13 and trisomy 18 with congenital heart disease. Until recently medical professionals were taught that T13 and 18 were "lethal conditions" that were "incompatible with life" for which measures to prolong life are therefore ethically questionable and likely futile. While the medical literature painted one picture, family support groups shared stories of the long-term survival of children who displayed happiness and brought joy along with challenges to families. Data generated from such care shows that surgery can, in some cases, prolong survival and increase the likelihood of time at home. The authors caution against a change from never performing heart surgery to always—we suggest that the pendulum of intervention find a balanced position where all therapies including comfort care and surgery can be reviewed. Families and clinicians should typically be supported and empowered to define the best care for their children and patients. Key concepts in communication and case vignettes are reviewed including the importance of supportive relationships and the fact that palliative care may serve as an additional layer of support for decision-making and quality of life interventions. While cardiac surgery may be beneficial in some cases, surgery should not be the primary focus of initial family education and support.